Congenital cystic adenomatoid malformation of the lung (CCAM) and Bronchopulmonary sequestration (BPS): Prenatal diagnosis, pre- and postnatal interventions, and early- and long-term outcome (14 years clinical experience with 60 patients) - Pott Bärtsch, Eva Maria (Ludwig-Maximilians-Universität München, 2009)
DEUTSCHE ZUSAMMENFASSUNG siehe PDF-Datei S. 7 (Teil I) und S. 111 (Teil II). /// ENGLISH ABSTRACT: BACKGROUND AND PURPOSE: Fetal cystic lung lesions, such as congenital cystic adenomatoid malformation of the lung (CCAM) and bronchopulmonary sequestration (BPS), were once considered rare and of poor prognosis. The advances in prenatal imaging and fetal therapeutic intervention techniques have contributed to a revision of this opinion. However, hardly any long-term investigation exists and prenatal predictive factors are still controversially debated with a lack of detail. This complicates adequate counseling of expectant parents and patients management. The goal of this research was four-fold: (1) to study the long-term outcome of children with prenatally detected congenital cystic lung lesions, (2) to compare the long-term outcome with the early outcome of the disease, (3) to determine prenatal ultrasonographic features which are prognostic for the outcomes, and (4) to compare the findings of this study with the data obtained by an extended statistical analysis of all major series of patients published in the literature. PATIENTS AND METHODS: This prospective cohort study, a long-term follow-up study, was conducted on 60 fetuses prenatally diagnosed with cystic lung lesions and ultrasonographically evaluated from 1988 through 2002 at the University of California, San Francisco (UCSF) Medical Center and at the University Hospital Großhadern of the Ludwig-Maximilians-University (LMU) Munich, Germany. Based on a follow-up questionnaire (see appendix of PDF-file for copy) with 39 questions, sent to the patients’ parents up to 14 years later, and a review of the patients’ medical records, clinical data were extracted about present and past respiratory and non-respiratory symptoms, therapeutic interventions, and imaging studies. Respiratory difficulties such as the requirement of ventilatory support or oxygen, recurrent respiratory infections, asthma, and/or limited physical endurance were categorized into four severity groups. The study patients were classified into five surgical intervention groups: (1) termination of pregnancy, (2) invasive fetal treatment, (3) neonatal surgery, (4) childhood surgery, and (5) no surgical intervention. Postoperative early and late complications were investigated. The outcome was grouped into (i) early neonatal outcome, (ii) interim childhood outcome, and (iii) final outcome. The age at improvement was evaluated. To identify prenatal predictors for the outcome, the children’s prenatal ultrasound data were retrospectively reviewed. Data about the size, (Stocker) type, and location of the lung lesion and the development of a hydrops fetalis, mediastinal shift, ascites, pleural and pericardial effusions, skin edema, placental thickening, polyhydramnios, and the fetal growth were extracted. All quantifiable parameters were categorized into four severity groups. The size of the mass was categorized into (i) small, (ii) moderate, (iii) large, or (iv) very large. The predictive value of each prenatal parameter examined in this study was compared with predictions published in the literature. All study data were analyzed using the Pearson's chi-square test, t-tests of the means, analysis of variance (ANOVA), and bivariate correlation. The Committee of Human Research approved the study (see appendix of PDF-file for approval letter). RESULTS: The survival rate in this study of 60 fetuses with cystic lung lesions was 94% (51 of 54 cases) to the exclusion of 4 terminated pregnancies and 2 deceased, untreated fetal treatment candidates. Three patients died after birth despite invasive fetal treatment due to advanced hydrops fetalis and delayed open fetal surgery. Of the 51 surviving children, 11 (22%) children had invasive fetal treatment, 12 (24%) were operated on as neonates, 15 (29%) were operated on in childhood, and 13 (25%) had no surgery. Invasive fetal treatment had a success rate of 79% (11/14) with hydrops regressions 1 to 3 weeks after intervention. Asymptomatic or only mildly affected after birth were 31 (61%) children, 4 (8%) neonates had moderate respiratory symptoms, and 16 (31%) had severe early respiratory difficulties. Prematurity had a considerable influence on the early respiratory difficulties (p<0.001), as well as on non-respiratory problems, such as failure to thrive (p<0.08). Fetuses with very large lung lesions, with a hydrops, or after fetal therapeutic intervention were at high risk of developing severe early respiratory symptoms and to deliver prematurely (p<0.003). However, the early respiratory symptoms usually resolved in the neonatal period (41%), in the first two years of life (34%), or less frequently, lately until four years of age (16%). Non-respiratory problems improved at about two years of age. Late postoperative complications, such as a pectus excavatum, a prominent thoracic scar, and/or a residual CCAM occurred in 8 (21%) of the 38 operated children, even after fetal surgery which is discussed in detail in the Case Report in Part II (see PDF-file). However, the final respiratory outcomes of the children were favorable and independent of the early course of the disease. At the last follow-up (mean: 5.9 years of age, maximum: 13.1 years of age), there were 94% of the children (48 of 51 survivors) at good health, which is an excellent long-term outcome. The cystic lung lesions were prenatally diagnosed at a mean gestational age of 20.7 ± 3.8 weeks and sonographically characterized as CCAM (51 cases), BPS (5 cases), and CCAM-BPS-hybrid (4 cases). The lung lesions finally became very large (18 cases), large (8 cases), moderate (14 cases), and small (13 cases); and 7 masses vanished on sonography. The degree of a mediastinal shift followed the size and growth pattern of the mass. During pregnancy 25% of the masses had increased, 35% kept the same relative size, and 40% regressed. The critical period of mass size increase for large lesions was at 22.3 ± 1.5 mean gestational weeks, followed by the critical period of potential hydrops development about one week later at 23.0 ± 3.2 mean gestational weeks (18.4 to 28.4 weeks’ gestation) in 13 fetuses with very large masses. Solid appearing Stocker type III lesions tended to regress more often with a better outcome than Stocker type I lesions with dominant rapidly filling cysts. A large final mass size, a high degree of a mediastinal shift, and the development of a hydrops (in particular skin edema, marked ascites, and placentomegaly) were the most important predictors of early respiratory difficulties, prematurity, and the requirement of pre- or postnatal surgical interventions (p<0.001 to p<0.01). However, unlike the early respiratory outcome, the respiratory long-term outcomes were independent of the prenatal predictors (p>0.3) and, with a few exceptions, they were excellent. CONCLUSION: The clinical impact of this study is a significantly improved patient counseling with updated pre- and postnatal management recommendations (see chapter 6.2 of PDF-file for details). Early respiratory symptoms of children prenatally diagnosed with a cystic lung tumor can be predicted by the size of the tumor. The mass size conditions all other pre- and postnatal symptoms. Close ultrasonographic prenatal monitoring during the period of critical mass size increase is recommended. Few fetuses develop very large masses. These are at high risk of developing a life-threatening hydrops and to deliver prematurely. The early detection of a hydrops is crucial to initiate timely fetal treatment, which increases the survival of hydropic fetuses. Even if the tumor is small and the child is asymptomatic, an elective postnatal early tumor resection is recommended. The majority of children are asymptomatic. Most of the early respiratory and non-respiratory symptoms resolve in the neonatal period or until the age of 2 years, and the long-term outcomes are excellent.